Progress in the Application of Carbon Dots-Based Nanozymes - Jin, Jun; Li, Linlin; Zhang, Lihui; Luan, Zhihui; Xin, Shuquan; Song, Kai (Frontiers in Chemistry, 2021)
As functional nanomaterials with simulating enzyme-like properties, nanozymes can not only overcome the inherent limitations of natural enzymes in terms of stability and preparation cost but also possess design, versatility, maneuverability, and applicability of nanomaterials. Therefore, they can be combined with other materials to form composite nanomaterials with superior performance, which has garnered considerable attention. Carbon dots are an ideal choice for these composite materials due to their unique physical and chemical properties, such as excellent water dispersion, stable chemical inertness, high photobleaching resistance, and superior surface engineering. With the continuous emergence of various Nanozymes Compositing Carbon Dots (NCCDs), it is vital to thoroughly understand their working principle, performance evaluation, and application scope. This review comprehensively discusses the recent advantages and disadvantages of NCCDs in biomedicine, catalysis, sensing, detection aspects. It is expected to provide valuable insights into developing novel NCCDs.